Activation of Dopamine D2 Receptor Suppresses Neuroinflammation Through αB-Crystalline by Inhibition of NF-κB Nuclear Translocation in Experimental ICH Mice Model. Issue 9 (September 2015) - Zhang, Yang; Chen, Yujie; Wu, Jiang; Manaenko, Anatol; Yang, Peng; Tang, Jiping; Fu, Weiling; Zhang, John H.
<x xml:space="preserve">Abstract</x> Background and Purpose— Inflammatory injury plays a critical role in intracerebral hemorrhage (ICH)–induced secondary brain injury. Recently, dopamine D2 receptor (DRD2) is identified as an important component controlling innate immunity and inflammatory response in central nervous system, and αB-crystallin (CRYAB) is a potent negative regulator on inflammatory pathways. Here, we sought to investigate the role of DRD2 on neuroinflammation after experimental ICH and the potential mechanism mediated by CRYAB. Methods— Two hundred and twenty-four (224) male CD-1 mice were subjected to intrastriatal infusion of bacterial collagenase or autologous blood. Two DRD2 agonists quinpirole and ropinirole were administrated by daily intraperitoneal injection starting at 1 hour after ICH. DRD2 and CRYAB in vivo knockdown was performed 48 hours before ICH insult. Behavioral deficits and brain water content, Western blots, immunofluorescence staining, coimmunoprecipitation (Co-IP) assay, and proteome cytokine array were evaluated. Results— Endogenous DRD2 and CRYAB expressions were increased after ICH. DRD2 knockdown aggravated the neurobehavioral deficits and the pronounced cytokine expressions. DRD2 activation by quinpirole and ropinirole ameliorated neurological outcome, brain edema, interleukin-1β, and monocyte chemoattractant protein-1 expression, as well as microglia/macrophages activation, in the perihematomal region. These effects were abolished by pretreatment with CRYAB siRNAs. Quinpirole enhanced cytoplasmic binding activity between CRYAB and NF-κB and decreased nuclear NF-κB expression. Similar therapeutic benefits were observed using autologous blood injection model and intranasal delivery of quinpirole. Conclusions— DRD2 may have anti-inflammatory effects after ICH. DRD2 agonists inhibited neuroinflammation and attenuated brain injury after ICH, which is probably mediated by CRYAB and enhanced cytoplasmic binding activity with NF-κB.